The sacred, the comic and Zen: a look at the poetry of Kobayashi Issa - Alape Vergara, Rosenberg (Estudios de Filosofía, 2014)
Although at first glance the comic and the sacred seem exclusive categories and, perhaps, opposite, throughout history we find examples where such human manifestations intertwine, both directly and forcefully. This article explores the relationship between these two categories in light of the use of sarcasm, irony, and hilarity present in the work of Kobayashi Issa, one of the great exponents of zen haiku. We begin with a definition of the essential features of the comic. Then we focus on the coexistence of humor and religious tradition of Zen, and finally we trace the sacred comedy in the work of the Japanese poet.